Development of data acquisition biogas monitoring system based on IoT - Dewi, Endang Purnama; Sumarsono, Joko; Amuddin, Amuddin; Kompyang, I Gusti Made (Jurnal Agrotek Ummat, 2024)
The development of microcontroller and semiconductor technology continues to increase in line with demands for system control and monitoring, including in the context of renewable energy. This control and monitoring process is also applied in biogas production. Conventional biogas plants in the field are not monitored so that communities face various challenges including a lack of organic material (low organic loading rate) and overload (excessive organic loading rate). Overloading slows or stops the anaerobic digestion process and can cause total system damage. Furthermore, another challenge that arises from inadequate or nonexistent monitoring of biogas plants is poor production due to excessive temperature fluctuations or inappropriate temperature ranges for various types of methanogenic bacteria. this research introduces an innovative monitoring system capable of accurately tracking several key parameters, including air temperature and humidity (DHT22), organic material temperature (DS18B20), and biogas pressure (MPX5700DP). This solution is built on the Internet of Things (IoT) concept, utilizing Arduino as the sensor data processor and Wemos D1 Mini as the wifi module connecting the system to the IoT platform, Cayenne. These findings provide valuable insights into the performance of the biogas installation during that specific time period. With the implementation of this monitoring system, it is anticipated that the efficiency and stability of biogas production can be improved through accurate and real-time monitoring of key variables in the biogas production process. Analysis of monitoring data reveals that the highest air temperature generally occurs during the daytime, particularly between 13:00 and 14:00, while the lowest air temperature is recorded in the morning around 05:00 to 06:00 on rainless days. Additionally, organic material temperature exhibits fluctuations, with the lowest point typically occurring between 06:00 and 09:00, and the highest point between 15:00 and 20:00. Biogas pressure reaches its peak on the sixth day, namely on January 10, 2022, at around 13:00, with pressure reaching 3.9 kPa.